ALCOHOLISM AND MENTAL HEALTH: A NURSING REFLECTION - Ari Nunes Assunção (Universidade Federal do Paraná, 1996)
It is sought to establish a bridge in thought concerning alcoholism and mental disease. A self-questioning is proposed regarding the nursing role nowadays. and how it might be turned into an instrument to intervene when facing these healt questions with which humanity greatli worries.